KOMUNIKASI INTERPERSONAL MELALUI PENGGUNAAN MEDIA SOSIAL ANTARA DOKTER DAN PASIEN DI KLINIK MEDIKA LESTARI JAKARTA - Satya Candrasari (UNIVED PRESS, Universitas Dehasen Bengkulu, 2019)
This research analyze in more detail the interpersonal communication between doctor and patient through social media at Medika Lestari Clinic. The role of social media is expected to be a central tool in order to improve health in the society. Interpersonal communication is key in order to provide health information for both patients and doctors or other medical personnel. Interpersonal communication that will be discussed is about the positive aspects that would have a significant impact for the progress of health services to the community. This research will take place at the Medika Lestari Clinic in Rawasari area. From this study it was concluded that interpersonal communication through social media Whatsapp between doctors and patients is very considering openness, empathy, supportive attitude, positive attitude, and equality.